L’irrigation en Inde rurale à l’épreuve de la décentralisation - Emmanuel Bon; Frédéric Landy (Développement Durable et Territoires)
Officially, the early 1990’s stands as a watershed as far as development planning and process are concerned in India. Both Central government and the States are seeking stakeholders’ participation in the management of common pool resources, especially water for irrigation. Beyond rhetoric’s, we do think that participation is seen as instrumental, i.e. as an easy way out to raise the overall efficiency of administrative interventions. Ultimately, decentralisation might not be a tool for local governance but a mere solution to both financial and legitimacy crisis of the State development planning.